2016
DOI: 10.5750/ejpch.v4i1.1073
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the Illness Perception Questionnaire in practitioners working with patients with co-morbid schizophrenia and learning disability

Abstract: Rationale, aims and objectives: The widely-used Illness Perception Questionnaire (IPQ) adapted for use in patients with major mental health problems and those who care and work with them, was originally developed for evaluating the illness perceptions of patients with physical pathology. There have been concerns expressed regarding the appropriateness of the IPQ and derivative measures of it in axis I disorders such as schizophrenia. The current investigation examined the measurement characteristics of a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…One [27] reported that, for the IPQ-R in German-speaking outpatients with chronic schizophrenia, the personal control and illness coherence subscales (Cronbach's α: 0.52, 0.48) did not have acceptable levels of internal consistency (> 0.70), but test-retest correlations in all subscales significant. Two others [9,28] also reported low Cronbach α values in treatment control and personal control in a test of the IPQ-R for healthcare professionals. Another two [3,12], however, reported satisfactory internal reliability for all IPQ-R subscales in a test for caregivers of relatives with schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…One [27] reported that, for the IPQ-R in German-speaking outpatients with chronic schizophrenia, the personal control and illness coherence subscales (Cronbach's α: 0.52, 0.48) did not have acceptable levels of internal consistency (> 0.70), but test-retest correlations in all subscales significant. Two others [9,28] also reported low Cronbach α values in treatment control and personal control in a test of the IPQ-R for healthcare professionals. Another two [3,12], however, reported satisfactory internal reliability for all IPQ-R subscales in a test for caregivers of relatives with schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…The current study sought to determine the psychometric robustness and applied utility of the IPQ-R (Moss-Morris et al , 2002) “causes” and “consequences” derived domains developed for PMH. Noteworthy prior to discussion of the empirical findings is that the focus on these particular domains was informed by work from a previous study (Jomeen et al , 2014), as per Fleming et al (2009) and Martin et al (2016) application of the IPQ-R sub-scales to mental health contexts is seemingly problematic in terms of measurement veracity, in a way which it is not in a physical health context (Arat et al , 2016) which may be fundamental to the underlying dimensional structure as envisaged by Moss-Morris et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional design and instrument evaluation approach taken to investigate the psychometric properties of the PIPS. Validity and reliability evaluation of the PIPS was undertaken using established statistical approaches (Kline, 2000; Martin and Savage-McGlynn, 2013; Martin et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Validity and reliability evaluation of the PIMMHS were undertaken using established statistical approaches [22][23][24] .…”
Section: Design and Participantsmentioning
confidence: 99%